A Brief Overview of Room Temperature Na‐S Batteries Using Composite Sulfur Cathode. Issue 1 (23rd August 2021) - Kumar, Deepak; Mishra, Kuldeep
Abstract: The research interests on sodium‐sulfur (Na‐S) batteries which have regained the worldwide attention from last few years. Na‐S battery technology seems a good choice for future grid level stationary energy storage units where the cost is as important as the performance from practical applications point of view. This paper summarizes basic principle of operation, major benefits, and challenges of room temperature Na‐S batteries using composite sulfur based cathodes. Few recent techniques employed by the research groups to develop composite sulfur cathodes for Na‐S batteries are highlighted including the guidelines for upcoming Na‐S batteries.